2014
DOI: 10.1177/0734242x14556527
|View full text |Cite
|
Sign up to set email alerts
|

Hazardous and toxic waste management in Botswana: Practices and challenges

Abstract: Hazardous and toxic waste is a complex waste category because of its inherent chemical and physical characteristics. It demands for environmentally sound technologies and know-how as well as clean technologies that simultaneously manage and dispose it in an environmentally friendly way. Nevertheless, Botswana lacks a system covering all the critical steps from importation to final disposal or processing of hazardous and toxic waste owing to limited follow-up of the sources and types of hazardous and toxic wast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 14 publications
0
32
0
1
Order By: Relevance
“…Many studies on hazardous and industrial waste from specific industries have been concentrated on waste characterization and management activities (Curran and Williams, 2012;Das et al, 2012;Mmereki et al, 2014). In fact, the first step for planning and developing a more adequate system of waste management is to study the quantity, type, and composition of industrial waste.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies on hazardous and industrial waste from specific industries have been concentrated on waste characterization and management activities (Curran and Williams, 2012;Das et al, 2012;Mmereki et al, 2014). In fact, the first step for planning and developing a more adequate system of waste management is to study the quantity, type, and composition of industrial waste.…”
Section: Introductionmentioning
confidence: 99%
“…In much of the African continent, waste disposal facilities are unregulated or uncontrolled. Although no figures have been provided in countries like Botswana, it has been observed that a significant proportion of HHW disposal occurs with inadequate control or treatment [8]. It is a common practice to dispose of HHW wastes in unregulated landfills, conventional landfilling.…”
Section: Collection and Disposalmentioning
confidence: 99%
“…Other harmful effects of HHW include air pollution, which may be caused by the release of mercury, lead, cadmium and nickel into the atmosphere from burning batteries [1]. In most of the African countries, inadequacies of the policy frameworks include lack of capacity and governance [8]; fewer resources available to deal with environmental health issues arising, limited expertise and knowledge on HHW management technologies, inappropriate HHW classification and characterization and municipalities have not created their own HHW database. On the other hand, developed countries have dedicated substantial economic resources to regulate the production, treatment and disposal of HHW [9].…”
Section: Introductionmentioning
confidence: 99%
“…The landfills were located at a distance away from the health facilities. The main idea of the landfill is storage and containment of the waste deposited into it (Mmereki et al 2017;Mmereki et al 2014]. However, how the landfills were operated in sharp contrast to normal procedures.…”
Section: Treatment and Disposal Of Wastementioning
confidence: 99%